Potential evaluation of agroindustrial waste from three passifloraces as a source of usable biomass (2018)
Colombia is the country with the highest biodiversity of species of the Passifloraceae family in the world, to date possess an inventory of 167 species. Some of these have a high commercial importance derived from their consumption in fresh and processed; reason why they are widely cultivated in different regions of the country, but especially distributed throughout the Andean Region. Because of the above it is evident that a significant part of the fruits used in the consumption generate by-products that are going to give to the landfills, becoming a focus of environmental contamination. Therefore, this project evaluated the potential of the byproducts generated from three Passiflorae edulis Sims, Passiflorae mollissima (Kunth) L.H. Bailey and Passiflorae quadrangularis L. for their potential use as biomass. For this purpose, fruits were used in consumption matures of the three-species forming a single batch and performing the analyzes of the variables in triplicate. Hence, the analysis of the content of holocellulose, cellulose, hemicellulose and lignin, as well as determination of the dry matter content and percentage of moisture by lyophilization and organic matter were carried out using a unifactorial design (residues of the studied fruit). Consequently, as a result of data processed in the Matlab statistical package through analysis of variance it was evidenced that the analyzed postharvest residues have a high potential in the three pasifloras evaluated as a source of usable biomass. Lastly, it is emphasized the pericarp of passion fruit (Passiflorae edulis Sims) becouse it showed higher percentage contents in the variables cellulose, hemicellulose and lignin what evidenced the potential of these residues (residual biomass) for the production of so-called " Biofuels - Second Generation". Copyright © 2018, AIDIC Servizi S.r.l.